2018
DOI: 10.1038/s41598-018-33661-y
|View full text |Cite
|
Sign up to set email alerts
|

RAGE deficiency does not affect non-alcoholic steatohepatitis and atherosclerosis in Western type diet-fed Ldlr−/− mice

Abstract: Non-alcoholic fatty liver disease is a spectrum of liver diseases ranging from steatosis only to non-alcoholic steatohepatitis (NASH). The latter is characterized by hepatic inflammation, which increases the risk of cardiovascular disease. It is poorly understood which factors contribute to the onset of hepatic inflammation characterizing the progression from steatosis to NASH. Previously, we demonstrated increased advanced glycation endproducts (AGEs) in the livers of NASH patients. We hypothesise that AGEs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Thus, although we could not completely rule out the possibility that the PKA signaling inactivation participates in the protective effects of RAGE deficiency on the liver of aging mice, the role of this signaling is limited. Bijnen et al (2018) claimed that RAGE-deficient mice displayed reduced weight gain and visceral fat expansion compared to control mice and RAGE does not play a major role in the development of NASH in a hyperlipidemic mouse model. Currently, although the reason for this inconsistency is unclear, the animal models and feeding conditions were different in the two studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although we could not completely rule out the possibility that the PKA signaling inactivation participates in the protective effects of RAGE deficiency on the liver of aging mice, the role of this signaling is limited. Bijnen et al (2018) claimed that RAGE-deficient mice displayed reduced weight gain and visceral fat expansion compared to control mice and RAGE does not play a major role in the development of NASH in a hyperlipidemic mouse model. Currently, although the reason for this inconsistency is unclear, the animal models and feeding conditions were different in the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, all these data indicate a critical role of RAGE in the regulation of hepatic steatosis. However, a recent study claimed that RAGE‐deficient mice displayed reduced weight gain and visceral fat expansion compared to control mice and RAGE does not play a major role in the development of NASH in a hyperlipidemic mouse model (Bijnen et al, 2018). As RAGE is widely expressed, the whole‐body deletion of RAGE might differ from the liver‐specific suppression of RAGE.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is also expressed on hepatic stellate cells, epithelial hepatocytes and Kupffer cells (19,20). However, its contribution to inflammatory liver disease is still an unresolved issue (21).…”
Section: Introductionmentioning
confidence: 99%
“… 54 In particular, plasma and liver levels of MGO were increased in RAGE −/− mice fed with a Western-type diet. 55 Also, it has been shown that HFD was associated with increased AGE levels in the liver, heart, and kidney of rats. 56 …”
Section: Discussionmentioning
confidence: 99%
“…54 In particular, plasma and liver levels of MGO were increased in RAGE −/− mice fed with a Western-type diet. 55 Also, it has been shown that HFD was associated with increased AGE levels in the liver, heart, and kidney of rats. 56 The role of AGEs, RAGE, and particularly their interaction has been in focus last decades due to the potential regulation of the NF-κB inflammatory pathway by AGE-RAGE.…”
Section: Discussionmentioning
confidence: 99%